PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Felmawati, Erik Noviana; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test the influence of liquidity, leverage, profitability and firm size to the stock return through the annual financial statement which has been prepared by food and Beverages Companies which are listed in Indonesia Stock Exchange. The independent variablesare current ratio, debt to equity ratio, return on asset and firm size. Meanwhile, the dependent variable is stock return. The population of this research has been obtained by using purposive sampling method on food and beverages companies which are listed in Indonesia Stock Exchange (IDX) during 2011-2015 periods and based on the predetermined criteria, 8 food and beverages companies have been selected as samples. The analysis method has been carried out by using multiple linear regressions analysis with the instrument application of SPSS (Statistical Product and Service Solutions). The result of this research shows that DER give significant and negative influence to the stock return with its coefficient regressions is -0.460 and the significance level is 0,000. Meanwhile, CR, ROA and firm size do not have any influence to the stock return. The coefficient determination (R2) has found that R square is 0.352 or 35.2% which means that the capability of the independent variables in explaining the dependent variable is very low and limited.Keywords: Liquidity, leverage, profitability, firm size, stock return.